Members of the RKD transcription factor family induce an egg cell-like gene expression program - Kőszegi, Dávid; Johnston, Amal Joseph; Rutten, Twan; Kirioukhova, Olga; Grossniklaus, Ueli; Bäumlein, Helmut (The plant journal, 2011)
In contrast to animals, the life cycle of higher plants alternates between a gamete-producing (gametophyte) and a spore-producing (sporophyte) generation. The female gametophyte of angiosperms consists of four distinct cell types, including two gametes, the egg and the central cell, which give rise to embryo and endosperm, respectively. Based on a combined subtractive hybridization and virtual subtraction approach in wheat (Triticum aestivum L.), we have isolated a class of transcription factors not found in animal genomes, the RKD (RWP-RK domain-containing) factors, which share a highly conserved RWP-RK domain. Single-cell RT-PCR revealed that the genes TaRKD1 and TaRKD2 are preferentially expressed in the egg cell of wheat. The Arabidopsis genome contains five RKD genes, at least two of them, AtRKD1 and AtRKD2, are preferentially expressed in the egg cell of Arabidopsis. Ectopic expression of the AtRKD1 and AtRKD2 genes induces cell proliferation and the expression of an egg cell marker. Analyses of RKD-induced proliferating cells exhibit a shift of gene expression towards an egg cell-like transcriptome. Promoters of selected RKD-induced genes were shown to be predominantly active in the egg cell and can be activated by RKD in a transient protoplast expression assay. The data show that egg cell-specific RKD factors control a transcriptional program, which is characteristic for plant egg cells.
Gesehen am 15.05.2017